2012
DOI: 10.1590/s0103-507x2012000400012
|View full text |Cite
|
Sign up to set email alerts
|

Insuficiência adrenal relativa como preditora de gravidade de doença e mortalidade do choque séptico

Abstract: ObjectiveTo evaluate if cortisol responses to 250 µg of intravenously administered adrenocorticotropic hormone are related to disease severity and, hence, mortality. MethodsThis is a retrospective study in a medical-surgical intensive care unit of a university hospital. We studied 69 consecutive patients with septic shock over a 1-yr period; these patients underwent a short 250-µg adrenocorticotropic hormone test because they exhibited >6 hours of progressive hemodynamic instability requiring repeated fluid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The median APACHE-II score was 26, and the median age was 81 years in this retrospective study. In other studies, patients with septic shock [ 17 19 ] with a respective mean APACHE-II score of 22, 20 and 24 had reported a median age of 57, 54 and 32 years, respectively. The higher APACHE-II score in this study could partly be explained by the advanced age of the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…The median APACHE-II score was 26, and the median age was 81 years in this retrospective study. In other studies, patients with septic shock [ 17 19 ] with a respective mean APACHE-II score of 22, 20 and 24 had reported a median age of 57, 54 and 32 years, respectively. The higher APACHE-II score in this study could partly be explained by the advanced age of the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality also had a significant difference in intervention shock which were given low dose of hydrocortisone, the mortality rate differed significantly (17). In a retrospective study on refractory septic shock with 28-day mortality of 55%, they concluded that higher basal cortisol level was related with higher mortality and response to cosyntropin test did not relate to outcome (18). In the last version of international guidelines for management of severe sepsis and septic shock, there is no recommendation for hydrocortisone administration in septic shock.…”
Section: Discussionmentioning
confidence: 99%